2021
DOI: 10.1055/s-0041-1730033
|View full text |Cite
|
Sign up to set email alerts
|

Use, Impact, Weaknesses, and Advanced Features of Search Functions for Clinical Use in Electronic Health Records: A Scoping Review

Abstract: Objective Although vast amounts of patient information are captured in electronic health records (EHRs), effective clinical use of this information is challenging due to inadequate and inefficient access to it at the point of care. The purpose of this study was to conduct a scoping review of the literature on the use of EHR search functions within a single patient's record in clinical settings to characterize the current state of research on the topic and identify areas for future study. Methods We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In general practice and emergency departments, up to one‐half of symptoms defy definitive diagnosis on first encounters 11 . Between 75% and 80% of such symptoms improve over four to 12 weeks, usually regardless of medical intervention 10 . Patients with “medically unexplained symptoms” should be spared exhaustive and fruitless testing for underlying rare diseases, and where normal results may still not allay patient discomfort and anxiety 12 .…”
Section: Questioning the Role Of Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In general practice and emergency departments, up to one‐half of symptoms defy definitive diagnosis on first encounters 11 . Between 75% and 80% of such symptoms improve over four to 12 weeks, usually regardless of medical intervention 10 . Patients with “medically unexplained symptoms” should be spared exhaustive and fruitless testing for underlying rare diseases, and where normal results may still not allay patient discomfort and anxiety 12 .…”
Section: Questioning the Role Of Testingmentioning
confidence: 99%
“…Affording clinicians more time and support to adequately perform basic clinical tasks is paramount 9 . Re‐engineering electronic medical records and laboratory reporting systems to enable more efficient searching for past diagnosis lists and test results 10 could also reduce diagnostic confusion and unnecessary testing, especially repeat requests of the same test.…”
Section: Questioning the Role Of Testingmentioning
confidence: 99%
“…A large-scale retrospective analysis of searches performed in an EHR found that the use of search varied considerably across and within user roles, with physicians and pharmacists being the most active user groups [ 19 ]. A review of the use of search within EHRs found that few articles focused on the impact of search within clinical workflows [ 23 ]; one study with 7 diabetes experts found that content-based search was both faster and more accurate than conventional search for finding relevant information [ 20 ], another study with 10 family and internal medicine physicians found that semantic search allowed for faster medical notes navigation for IR tasks [ 21 ], and a final study with 4 students found that a semantic search tool enabled faster clinical note summarization [ 22 ]. Only one of the described studies [ 20 ] used a crossover study design.…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale retrospective analysis of searches performed in an EHR found that the use of search varied considerably across and within user roles, with physicians and pharmacists being the most active user groups [19]. A review of the use of search within EHRs found that few articles focussed on the impact of search within clinical workflows [23]; one study with 7 diabetes experts found that content-based search was both faster and more accurate than conventional search for finding relevant information [20], another study with 10 family and internal medicine physicians found that semantic search gave faster medical notes navigation for IR tasks [21], and a final study with 4 students found that a semantic search tool enabled faster clinical note summarisation [22]. Only one of the described studies [20] used a crossover study design.…”
Section: Introductionmentioning
confidence: 99%